Contribuições dos espaços não formais para o ensino e aprendizagem de ciências de crianças com Síndrome de Down - Pina, Onilton Cézar (2014)
This work aims to analyze the possible contribution of non-formal spaces for the learning of science by children with Down Syndrome (DS). In the first part, we try to understand what this syndrome is and how the cognitive development and learning of people with Down happens. You can notice that this subject experiences the same stages of cognitive development that other individuals who do not have the syndrome do, such as: sensorimotor, concrete operations and formal operations. In the second part, we analyze the non-formal spaces and science teaching and learning by children with Down. It was found that these spaces are an important resource for the development of educational activities and are exploited, increasingly, seeking to break the limits of school space, in search of more meaningful knowledge. For this reason, we present some non-formal spaces of the city of Goiania. Among them, we have evaluated the potential of the Museu de História Natural in Memorial do Cerrado, from the speech of an educational agent / mediator / monitor of this museum space and some teachers who visit this place with children, some with DS. After the research, we can ensure that the use of non-formal spaces for teaching children with Down Sciences, when well directed and harnessed as expected by the designers, serves very well to the teacher's expectations and thus facilitates learning.